Implementasi Metode Simple Additive Weighting (SAW) Pada Sistem Seleksi Penerimaan Calon Karyawan Baru (Studi Kasus : PT. Dalang Digital Studio) - Sifa Pradina (CV. Multi Kreasi Media, 2023)
Employee selection is the process of selecting the right employees according to the needs expected by the company so that these employees can work optimally so that they can increase company productivity and can survive in the company for a long time. Therefore, the selection process for recruiting new employees is very important for companies to get qualified employees with special skills that suit the company's needs. In this study, the Simple Additive Weighting (SAW) method was used as a method in the selection system for new employees. The purpose of this research is to build a new employee recruitment selection system at PT. Dalang Digital Studio and applies the Simple Additive Weighting (SAW) method. The use of the Simple Additive Weighting (SAW) method in the new employee recruitment selection system so that the new employee recruitment selection process becomes more objective, and to minimize errors in the decision-making process.Because compared to other decision-making models, the Simple Additive Weighting (SAW) method is based on the criteria value and preference weights directly from the company, resulting in a more accurate assessment and ranking process after determining the weight value for each attribute can choose the best alternative from a set of alternatives. there is. Based on the implementation and testing of applying the Simple Additive Weighting (SAW) method to the selection system for the acceptance of new employees. The selection system for new employee candidates becomes more objective and can help personnel to minimize errors in the decision-making process.